Sports anthropogenetics - limitative sport success factors (literature review) - Semenov, M. M.; Kobelkova, I. V.; Sorokina, E. Yu.; Vybornaya, K. V.; Baryshev, M. A.; Nikityuk, D. B. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
Current sports anthropogenetics data and relationship between genes polymorphisms and limitative sport success factors published in 2016-2018 were considered As result of our analysis, all literature sources were systematize in promising fields of investigates; their contribution in the anthropogenetics development was calculate. Generally, researches are dedicated to the study of the relationship between genes polymorphisms and sports injuries and physical abilities, because professional sports are associated with various etiology injuries.